Information System Success Model Analysis - Enhancing User Satisfaction in Video Streaming Platforms Using Video Streaming Analytics Features - Nugraha Budi Samawi; Leo Aldianto (Universitas KH. Abdul Chalim Mojokerto, 2025)
The swift expansion of Subscription Video on Demand (SVoD) platforms in Indonesia is resulting in user retention challenges; data indicates that 23% of users plan to terminate their subscriptions. This research study examines the determinants of user happiness with the objective of giving pragmatic methods to mitigate subscription cancellation rates. The foundational principle of this research study is the Delone & McLean Information System Success Model. This theory elucidates the quality of the system, the quality of information, and the quality of service, which are identified as critical factors of user satisfaction and will ultimately influence the net benefits. This study employed a quantitative methodology, gathering data from 186 Indonesian SVoD respondents and analysing it by Partial Least Squares Structural Equation Modelling. The analysis results indicate a substantial beneficial impact of system quality, information quality, and service quality on user happiness. User happiness influences net benefits, which can lead to user retention and market expansion. To address the problem of subscription cancellation business, this research study proposes a Video Streaming Analytics (VSA) system. The proposed VSA solution is a surveillance system to collect real-time information about video streaming KPIs. VSA uses machine learning models to improve network performance and can be used for personalization. The next step after implementing VSA is to use the information collected to create licenses and partnerships according to Indonesian user trends and preferences. By implementing VSA and personalized campaigns, SVoD platforms and telecom service providers can improve their user satisfaction and further reduce churn rates and tap into the potential of Indonesia's entertainment content market. This research study emphasizes analytics-based strategies to create competitive advantage and long-term sustainability in the industry.